Nutritional status and nutrient intake from complementary foods among breastfed children in Purworejo District, Central Java, Indonesia - Endang Dewi Lestari; T Ninuk S Hartini; M Hakimi; A Surjono (Indonesian Pediatric Society Publishing House, 2016)
Background The growth rate of Indonesian infants beyond six months of age declines compared with that of the international reference population. Objective This study aimed to describe the pattern of nutritional status among breastfed children and their intake of energy, pro- tein, and zinc from complementary foods in Purworejo District, Cen- tral Java, Indonesia. Methods The study was a cross sectional survey drawing breastfed children under 24 months old from a well-defined population. Chil- dren with a history of prematurity or low birth weight were excluded. Anthropometrical measurements were collected. Intake of comple- mentary food was assessed using 24-hour recall. Analysis of nu- tritional intake was only performed in 11-23 month-old children. Results Of 577 children enrolled, the prevalence of underweight, stunting, and wasting were 8.1%, 8.8%, and 4.6%, respectively. The prevalence of undernutrition increased with age. There was no association between frequency of breastfeeding during 24 hours in the second year of life and the nutritional status. The average intake of energy, protein, and zinc from complementary foods was very low i.e., 30%, 45%, and 5% of the Indonesian recommended dietary allowance (RDA), respectively. Conclusion The prevalence of undernutrition in breastfed chil- dren increases with age. The breastfed children beyond 11 months of age in Purworejo District need sufficient density of nutrients from complementary foods.